Synthesis and biological evaluation of chrysin derivatives containing α-lipoic acid for the treatment of inflammatory bowel disease - Zhao, Pengyu; Hou, Yusen; Yan, Tingting; Kang, Jie; Tian, Ye; Li, Jiaxin; Zeng, Chenjuan; Geng, Funeng; Liao, Qi (Frontiers in Chemistry, 2024)
This study introduces newly discovered chrysin derivatives that show potential as candidate molecules for treating inflammatory bowel disease (IBD). Compound 4b, among the synthesized compounds, displayed significant inhibitory effects on monocyte adhesion to colon epithelium induced by TNF-α, with an IC50 value of 4.71 μM. Further mechanistic studies demonstrated that 4b inhibits the production of reactive oxygen species (ROS) and downregulates the expression of ICAM-1 and MCP-1, key molecules involved in monocyte-epithelial adhesion, as well as the transcriptional activity of NF-κB. In vivo experiments have shown that compound 4b exhibits a dose-dependent inhibition of 2, 4, 6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats, thereby validating its effectiveness as a colitis inhibitor in animal models. These results indicate that 4b shows considerable promise as a therapeutic agent for managing IBD.